The Effectiveness of Creative Problem Solving Through Concrete Media Towards Creative Thinking Skill of the Fourth Grade Students at SDN 1 Kaliombo - Puspita Yasa; Lintang Kironoratri; Lovika Ardana Riswari (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
The process of learning mathematics only focuses on understanding students but have not been able to develop their creative way of thinking. Students do not have the opportunity to explore answers or ways that are different from what the teacher teaches, so students cannot be creative in finding answers. The application of the creative problem solving learning model and concrete media in the form of nets of cubes and blocks is one solution to this problem. The purpose of this research is to find out: the difference in the average value of creative thinking skills after using the creative problem solving model and concrete media for fourth-grade students at SDN 1 Kaliombo. The experimental approach used in this research is the Pre-Experimental Design model in the form of a Pretest-Posttest Group Design. This study used fourth-grade students at SDN 1 Kaliombo as subjects, taking samples using total sampling or census. The research data was obtained from a statistical analysis of the t-test in the form of a Paired Sample t-Test. This study shows that: there is a difference in the average value before and after using the creative problem solving model and concrete media with a significance of 0.000 <0.025. Therefore, the CPS model assisted by concrete media can be said to have an effect on students' creative thinking abilities.